2016
DOI: 10.7717/peerj.1620
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early and late cheiloplasty on anterior part of maxillary dental arch development in infants with unilateral complete cleft lip and palate

Abstract: Objectives. The objective of this study is to compare the impact of early and late reconstruction of complete unilateral cleft lip and palate on the growth and development of the front of the dentoalveolar arch. Methods. This study was carried out in the years 2012–2015 at the Clinic of Plastic, Reconstructive and Aesthetic Surgery in Banska Bystrica. Infants with unilateral complete cleft lip and palate were divided into 2 groups according to the timing of lip reconstruction. Group A consisted of infants with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The second reason could be the different weaning policy according to institutional guidelines in both neonatal departments. Longer duration of surgery in hospital B could be due to the fact that there was a special otolaryngology team in hospital B and before every surgery 3 dimensional measurements of the palate were done (Valentova-Strenacikova and Malina, 2016). Although the differences in length of surgery and artificial ventilation during and after surgery were statistically significant, these may not probably have a significant influence on clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The second reason could be the different weaning policy according to institutional guidelines in both neonatal departments. Longer duration of surgery in hospital B could be due to the fact that there was a special otolaryngology team in hospital B and before every surgery 3 dimensional measurements of the palate were done (Valentova-Strenacikova and Malina, 2016). Although the differences in length of surgery and artificial ventilation during and after surgery were statistically significant, these may not probably have a significant influence on clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies verified angular measurements in palatal development of children with cleft lip and palate. The 1-year postcheiloplasty angular measurements have demonstrated a significant reduction of the values, even using different anatomic points 10–12 …”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49][50] It has been demonstrated that cleft lip repair mainly affects the anterior width of the maxilla by exerting continuous pressure, with little effect on the posterior width. 42,43,[48][49][50] The raising of mucoperiosteal flaps plus secondary healing process with scarred tissue formation in the lateral denuded areas could result in narrowing of the posterior maxillary width. 14,17,40,42,44 Therefore, patients with repaired unilateral cleft lip and palate generally present with a more severe transverse constriction of the posterior maxillary region compared with children with repaired unilateral cleft lip, 14,17,39,40,42,44 demonstrating that the palatoplasty could lead to restriction of the transverse development in the posterior region.…”
Section: Discussionmentioning
confidence: 99%
“…32,46 Because of the absence of maxillary arch continuity and lateral displacement of the maxillary segments in unilateral cleft lip and palate deformity, children with this particular form of cleft present wider transverse maxillary dimensions before primary operations compared with children with an isolated cleft lip deformity. [47][48][49][50] It has been demonstrated that cleft lip repair mainly affects the anterior width of the maxilla by exerting continuous pressure, with little effect on the posterior width. 42,43,[48][49][50] The raising of mucoperiosteal flaps plus secondary healing process with scarred tissue formation in the lateral denuded areas could result in narrowing of the posterior maxillary width.…”
Section: Discussionmentioning
confidence: 99%